Case report: Highly response to low-dose brachytherapy in recurrent retroperitoneal leiomyosarcoma with FANCD2 frameshift mutation: a unique case study - Liu, Xiao li; Zhao, Jinxin; Di, Xue min; Cao, Guohui; Zhang, Hongtao; Wang, Juan (Frontiers in Oncology, 2024)
We report a case of recurrent retroperitoneal leiomyosarcoma in a male who achieved a rapid and robust but transient clinical response to low-dose iodine-125 brachytherapy. A FANCD2 frameshift mutation was detected by gene sequencing in the cancerous tissue.